Numerical evaluation of concrete time-dependent effects on urban cofferdams (2018)
Current construction methods for high-rise buildings combine a temporary cofferdam structure with top-down excavation techniques. The cofferdam allows the construction of the building rigid concrete core foundations in deep competent soil. In urban areas, excavation-induced ground movements must be controlled to protect adjacent infrastructure. Typically, urban cofferdams limit ground deformations via circular ring beam bracings made of either steel profiles or cast-in-place reinforced concrete. Concrete ring beams are nowadays becoming popular as they are directly placed in contact with the sheet piles, eliminating potential gaps between the lateral bracings and the retaining wall, and presumably reducing the amount of excavation-induced ground deformations. This research work presents a parametric study to evaluate time-dependent effects in an urban cofferdam braced with reinforced concrete ring beams. This is the first time where a fully couple numerical approach, considering aging, creep and shrinkage effects in the concrete along with advanced constitutive soil models to adequately represent consolidation and non-linear soil behavior, is presented. The parametric study is based on a numerical model calibrated and validated against field performance data collected during the construction of an urban cofferdam braced with seven reinforced concrete ring beams. The numerical approach proposed in this work allowed to isolate concrete time-dependent effects and the impact of related construction activities. It was found that aging effects were the most important concrete time-dependent component in the cofferdam performance. Aging induced-deformations for the considered case represent about 15% of the total horizontal displacements as calculated from the base model. Creep and shrinkage effects contribute around 6 and 3 %, respectively